Clays and Clay Minerals, Vol. 55, No. 4, 402–422, 2007. - Kadi˙r, Selahatti˙n (The Clay Minerals Society, 2007)
Pliocene volcaniclastic lacustrine rocks of the Dog˘anbey formation in the Beysehir region (central Anatolia) are composed of organic-matter-bearing claystone, clastic units and dolomite interbeds, suggesting an anaerobic, shallow swampy, lacustrine depositional environment. The depositional environment was subjected to periodic climatic change during which diagenesis occurred, and smectite, and locally palygorskite, were precipitated. Smectite flakes formed authigenically on feldspar and palygorskite fibers between dolomite rhombs and at the edges of smectite flakes. Increases in leaching of Na, K, Sr, Ba and Rb, increasing Al/Si ratios, and Fe with increasing degree of alteration reveal that hydration of volcaniclastic grains (feldspar, glass) by meteoric water - determined from O and H isotopic values - was the main cause of precipitation of beidellite and montmorillonite based on the tetrahedral charge/octahedral charge ratio, with average structural formulae of (Si7.72Al0.28)(Al3.20Fe0.53Mg0.25 Mn0.02Ti0.04)(Ca0.11Na0.09K0.11), and (Si7.88Al0.13)(Al3.18Fe0.53Mg0.18Mn0.02Ti0.05)(Ca0.11Na0.11K0.09), respectively. Therefore, the Dog˘anbey-area smectite is presumed to have formed by chemical weathering and dissolution-precipitation fromfeldspar and glass during diagenesis; palygorskite formed by direct precipitation from Mg-rich solutions during dolomitization, and by transformation from smectite in an alkaline lacustrine environment.
Mineralogy, Geochemistry And Genesis Of Smectite In Pliocene Volcaniclastic Rocks Of The Dog˘anbey Formation, Beysehi˙r Basin, Konya, Turkey
Clays and Clay Minerals, Vol. 55, No. 4, 402–422, 2007. Mineralogy, Geochemistry And Genesis Of Smectite In Pliocene Volcaniclastic Rocks Of The Dog˘anbey Formation, Beysehi˙r Basin, Konya, Turkey. Selahatti˙n Kadi˙r. DOI: 10.1346/CCMN.2007.0550408. Copyright © 2007, The Clay Minerals Society
Keywords: Periodicals; Geology; Geochemistry; Lacustrine Environment; Mineralogy; Smectite; Stable Isotopes; Turkey; Volcaniclastic Rocks